HONEY, HE SHRUNK THE KIDS: SWIFT AND IRISH WRITING - Declan KIBERD (Studia Universitatis Babeş-Bolyai. Philologia, 2018)
Honey, He Shrunk the Kids: Swift and Irish Writing. A study about Jonathan Swift as a founder of Anglo-Irish literature and of children’s literature, this paper delves into the “story of the repressed” and is an insight into the painful motivations that make the child-adult relationship an examination of human nature’s darker side of nature. This sub-genre considers the exploit of the defamiliarising effect in the tradition and types common in fairy tales of Gaelic Ireland and shows the Irish writer as a dissident and an upholder of tradition. The probability that his writing is the disclosure of any story’s potentiality is assumed by questing the welded joint of the relativity of all judgments, the extreme self-confidence of those who live at either extreme, the critique of unreasoning, tyranny and absence of rational justification of power systems.